2000
DOI: 10.1111/1099-1123.00308
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Audit Fees: Evidence from the Companies Listed in Bahrain

Abstract: This paper examines the audit fee structure in Bahrain for 38 companies listed on the Bahrain Stock Exchange (BSE). Data was collected from the BSE Directory and also from the listed companies. The study also provides data on the audit firms operating and listed with clients in Bahrain. Five variables, namely total assets (size), risk, complexity, timing of audit, and profitability were examined in relation to audit fees. A regression model was developed of the determinants of audit fees. The study strongly co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
67
6
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 12 publications
13
67
6
4
Order By: Relevance
“…Auditors need to make more efforts with a client with poor financial condition to avoid lawsuits against audit firms in the future, and thus, auditors will charge higher audit fees. Previous literature on the determinants of audit fees reported significant association with corporate risk (Simunic, 1980;Francis & Stokes, 1986;Joshi & Bastaki, 2000;Gonthier-Besacier & Schatt, 2007). However, several studies reported insignificant relationship between the two variables (Vermeer et al, 2009;Ellis and Booker, 2011).…”
Section: Second-level Headingmentioning
confidence: 94%
See 4 more Smart Citations
“…Auditors need to make more efforts with a client with poor financial condition to avoid lawsuits against audit firms in the future, and thus, auditors will charge higher audit fees. Previous literature on the determinants of audit fees reported significant association with corporate risk (Simunic, 1980;Francis & Stokes, 1986;Joshi & Bastaki, 2000;Gonthier-Besacier & Schatt, 2007). However, several studies reported insignificant relationship between the two variables (Vermeer et al, 2009;Ellis and Booker, 2011).…”
Section: Second-level Headingmentioning
confidence: 94%
“…Companies with several subsidiaries are considered to be more complex than companies with few or without subsidiaries. A significant proportion of previous studies observed positive relationship between corporate complexity and audit fees (Simunic, 1980;Brinn et al, 1994;Cameran, 2005;Joshi & Bastaki, 2000;Clatworthy & Peel, 2006;Thinggaard & Kiertzner, 2008;Vermeer et al, 2009;Ellis & Booker, 2011;Verbruggen et al, 2011). The main reasons advanced in the literature to explain such a relationship is that greater number of subordinate financial statements require more audit time and greater expertise to ensure the accuracy of the consolidated financial statements (Sandra & Patrick, 1996).…”
Section: Complexitymentioning
confidence: 96%
See 3 more Smart Citations